Sustainable career and employability of student leaders in China - Bai, Bin; Li, Mixue; Lyu, Xinshan (Frontiers in Psychology, 2022)
Research has shown that most employers prefer employing graduates with student leadership experience in colleges and most of student leaders have sustainable development in their career in China. Comparing with students without leadership experience, student leaders are easier to get promotion and development opportunities in workplace. To discuss this question, researchers chose employers, student leaders and teachers as research participants in an effort to answer the question of why employers prefer graduates with experience of being student leaders. This study focuses on what key competences student leaders possess and how their competences can match the capability requirement of employers. Semi-structured interviews were conducted with 9 outstanding student leaders, 4 class teachers, 2 student affairs administrators and 8 human resource managers from two vocational colleges in Beijing. We find that student leaders have strong social competence, emotional competence, action competence and responsibility and resilience which employers value and these competences are essential to career development in the workplace. These competences are considered to be helpful to support student leaders to adapt to the real work environment quickly and achieve career success.